Sagot :
Answer:
16. 3x^2 + 4xy + y^2
17. 3x^2 + 2xy - y^2
18. y^2 +2y -15
19. 2y + 6
20. y^2 -8y +15
Step-by-step explanation:
Using FOIL method:
16. (3x + y) (x + y)
3x^2 + 3xy + xy + y^2 (combine like terms)
= 3x^2 + 4xy + y^2
17. (3x - y) (x + y)
3x^2 +3xy -xy -y^2 (combine like terms)
= 3x^2 + 2xy - y^2
18. (y + 5) (y - 3)
y^2 -3y +5y -15 (combine like terms)
= y^2 +2y -15
19. (7-5) (y + 3)
7y + 21 -5y -15 (combine like terms)
= 2y + 6
20. (y-5) (y-3)
y^2 -3y -5y +15 (combine like terms)
= y^2 -8y +15